Experimental Evaluation of Physical, Mechanical and Chemical Properties of Natural and Recycled Concrete Aggregates - Chaurasiya, Anup Kumar; Aryal, Binod; Bhandari, Chakra; Joshi, Buddhi Raj; Aryal, Rajendra; Gautam, Prakash; KC, Narayan; Banjara, Santosh; Mishra, Dhirendra (Himalayan Journal of Applied Science and Engineering, 2025)
The structural properties of concrete, such as workability, strength, serviceability, and durability, are heavily influenced by the quality and characteristics of the aggregates used. The growing urbanization and infrastructure development have led to the overexploitation of natural aggregates, especially from the ecologically sensitive Chure region of Nepal, causing deforestation, habitat loss, and geomorphological instability. Meanwhile, construction and demolition waste continues to rise without effective reuse or regulation. This study addresses these challenges by evaluating the potential of Recycled Concrete Aggregates (RCA) as a sustainable alternative to Natural Aggregates (NA) for building applications. The research investigates and compares the physical (bulk density, specific gravity, water absorption, porosity), mechanical (aggregate crushing value, impact value), and chemical properties (alkali, chloride, sulfate, and carbonation content) of RCA and NA, following IS and ASTM standards. Assessing the physical, mechanical, and chemical properties of aggregates before concrete production is a critical step to ensure the quality, workability, strength, serviceability, and durability of the final concrete product.  The results revealed that RCA has lower bulk density and specific gravity, and significantly higher porosity compared to NA. While both aggregate types met acceptable limits for water absorption and most chemical contents, RCA exceeded the 5% limit for carbonation, posing risks in reinforced concrete. RCA also displayed higher mechanical properties – Aggregate Crushing Value (33.64% average) and Aggregate Impact Value (30.40% average), making it unsuitable for wearing surfaces but acceptable for general concrete use. The findings suggest that RCA, despite its limitations in density, porosity, and carbonation resistance, is a viable and eco-friendly option for non-structural applications, pavements, and general concrete works. Its adoption can reduce reliance on quarrying, conserve the Chure ecosystem, and promote sustainable construction in Nepal. However, standardized guidelines and public awareness are essential to enhance its effective use and address associated environmental and technical concerns.